Securing National Interests in The Global Information Space: International Experience and Implications for Uzbekistan - Rajabov Habibullo Ibodullayevich (Scientific Trends, 2025)
Any country seeking to ensure its security, peace and sustainable development must consider the protection of its national interests as its first priority. In this regard, ensuring national interests in the global information space is a priority. The article presents the experience of developed countries to protect national interests in the information space and analyzes the possibility of applying this experience in the practice of Uzbekistan.
Keywords: Information factor, global information space, interest, personality, public and state interests, national interests.